Kesiapsiagaan Individu-Rumah Tangga dan Kelembagaan Masyarakat Dalam Menghadapi Bencana Longsor Lahan Di Kecamatan Ngargoyoso Kabupaten Karanganyar Tahun 2019 - Muchtarom - Muctharom (Universitas Sebelas Maret (UNS), 2023)
This study aims (1) to know the level of preparedness of individuals - households in the face of landslides in the District Ngargoyoso Karanganyar and (2) to know the level of preparedness of community institutions in the face of landslides in the Ngargoyoso District, Karanganyar Regency.This researchy resulted the following conclusions. First, the level of individual-household preparedness in Ngargoyoso District is almost ready with 63 points. Ngargoyoso has 1 village with an individual-households preparedness level facing landslides with a very ready category, namely Kemuning with 80 points. Three villages have a level of preparedness with a ready category, namely Girimulyo with 67 points, Ngargoyoso with 71 points, and Segorogunung with 73 points. Two villages have a level of preparedness almost ready, namely Berjo with 60 points and Dukuh with 64 points. Three villages had a low level of preparedness, namely Jatirejo with 50 points, Nglegok with 49 points, and Puntukrejo with 50 points. Second, the level of community institutions preparedness to face landslides in Ngargoyoso District is almost ready with 58 points. Six villages in Ngargoyoso have the level of community institutions preparedness to face landslides in the almost ready category, namely Berjo (63 points), Dukuh (59 points), Girimulyo (64 points), Kemuning (61 points), Ngargoyoso (59 points), Nglegok (60 points); while three other villages in the category of less ready, namely Jatirejo (54 points), Puntukrejo (53 points), and Segorogunung (52 points).